Dendrocalamus asper (Buluh Betong) as raw material to manufacture wood plastic composite (WPC) / Nur Farhana Mohd Zailani - Mohd Zailani, Nur Farhana (2013)
Bamboo has been recognized as the second importance non- timber forest product by Malaysian Government. It can be a good substitute for timber in producing high value added products. For this reason, this study used Dendrocalamus asper as raw material to manufacture wood plastic composite. This study focused on the effect of particle size and the effect of Maleic Anhydride Grafted Polypropylene (MAPP) additive on physical and mechanical properties of wood plastic composite filled with 10 percent of Dendrocalamus asper sawdust. Three different particle size was been used which were 150µm, 180µm and 425µm in size. Particle size showed a significant influenced on physical and mechanical properties of the wood plastic composite board while the addition of 3 percent MAPP enhanced the physical properties and almost overall mechanical properties of wood plastic composite.